Direct Thrombin Inhibition with Rec-Hirudin CGP 39393 as Prophylaxis of Thromboembolie Complications after Total Hip Replacement - Eriksson, Bengt I; Kälebo, Peter; Ekman, Steffan; Lindbratt, Siv; Kerry, Roger; Close, Philippe (Thrombosis and Haemostasis, 1994)
Hirudin is an anticoagulant originally extracted from the leech Hirudo medicinalis. Using recombinant DNA technology a new compound, recombinant desulphato hirudin CGP 39393 has now been produced. The aim of this study was to determine the maximum tolerated dose in patients undergoing elective hip replacement. This open safety trial represents, to our knowledge, the first experience of recombinant hirudin in orthopedic patients.In this study 48 patients undergoing primary total hip replacement were included and the safety of subcutaneous injections of 10, 15, 20 and 40 mg CGP 39393 twice daily, was evaluated. Prophylaxis was started immediately pre-operatively and continued for 8-10 days. A mandatory bilateral phlebography was performed at the end of the prophylactic treatment period and a clinical follow-up was done 6 weeks after surgery.A major bleeding event occurred in the first 3 patients receiving 40 mg CGP 39393 b.i.d. and the prophylaxis regimen at this dosage level was therefore discontinued. Median values of total blood loss and requirements of blood transfusion in the patients receiving 10-20 mg CGP 39393 were similar to those reported in previous studies on total hip replacement performed at the same centre, using other prophylactic drugs. Deep vein thrombosis (DVT) was confirmed by phlebography in 5 out of 12 patients in the 10 mg group (41.7%, 95% confidence limits [CL]: 15.2-72.3%), 1 out of 11 patients in the 15 mg group (9.1%, CL: 0.23-41.3%) and 2 out of 20 patients in the 20 mg group (10.0%, CL: 1.2-31.7%) during the prophylaxis period.CGP 39393 was safe and well tolerated, when administered as subcutaneous injections of 10-20 mg twice daily. The dose level of 40 mg CGP 39393 twice daily resulted in serious disturbance of the hemostasis in patients after hip prosthesis surgery.